2004
DOI: 10.1046/j.1600-079x.2003.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptor agonist 2‐iodomelatonin prevents apoptosis of cerebellar granule neurons via K+ current inhibition

Abstract: Activation of K(+) current plays a critical role in the control of programmed cell death. In the present study, whole-cell patch-clamp recording, a caspase-3 activity assay, and flow cytometric analysis were used to examine the effects of the MT2 melatonin receptor agonist 2-iodomelatonin on the delayed-rectifier K(+) current (IK) and the prevention of apoptosis. It was found that apoptosis of cerebellar granular neurons induced by low-K(+) (5 mm) incubation was associated with an increase in IK amplitude and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 28 publications
5
57
0
Order By: Relevance
“…It is well known that K + channel-mediated signals play an important role in cell death or apoptosis (Jiao et al, 2004;Yu et al, 1997). We next examined whether the H 2 O 2 -induced increase in BK currents was associated with H 2 O 2 -induced cell injury.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that K + channel-mediated signals play an important role in cell death or apoptosis (Jiao et al, 2004;Yu et al, 1997). We next examined whether the H 2 O 2 -induced increase in BK currents was associated with H 2 O 2 -induced cell injury.…”
Section: Resultsmentioning
confidence: 99%
“…Among the different types of voltage-dependent potassium channels (K V ), the I K channels are thought to play important roles in apoptosis due to their high K + conductance and their slow or non-inactivation behaviour (Jiao et al, 2004;Yu et al, 1997). The K Ca current, which is associated with apoptosis, has been reported in a wide variety of cells (Krick et al, 2002;Ma et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that regulation of timing and quantity of apoptotic cells by melatonin requires both MT subtypes. Several studies already indicated that melatonin exerts effects on apoptosis via its receptors [70][71][72][73]. However, to our knowledge, the present study is the first to show that actually both, MT1 and MT2, are required for a specific functional role of melatonin within apoptosis under physiological conditions, namely the proper timing of diurnal changes in the number of apoptotic cells in the brain and pituitary.…”
Section: Mt1/2-mediated Changes In Apoptosismentioning
confidence: 41%
“…Bcl-2 is capable of blocking the apoptotic pathway in the mitochondria by preventing the formation of a functional mitochondrial permeability transition pore (mtPTP) and, thus, the release of the mitochondrial enzyme cytochrome c, which represents the fi nal and no-return signal of the apoptotic program (Khandelwal et al 2011 ). Studies in vitro indicate that melatonin enhances expression of Bcl-2 and prevents apoptosis (Jiao et al 2004 ;Koh 2011 ;Radogna et al 2010 ). In addition, melatonin directly inhibits the opening of the mtPTP, thereby rescuing cells (Peng et al 2012 ;Jou 2011 ;Andrabi et al 2004 ).…”
Section: Basic Biology Of Melatonin Relevant To Neurodegenerationmentioning
confidence: 99%